Mutational Analysis of the Nsa2 N-Terminus Reveals Its Essential Role in Ribosomal 60S Subunit Assembly - Paternoga, Helge; Früh, Alexander; Kunze, Ruth; Bradatsch, Bettina; Baßler, Jochen; Hurt, Ed (International journal of molecular sciences, 2020)
The ribosome assembly factor Nsa2 is part of the Rea1-Rsa4-Nsa2 interconnected relay on nuclear pre-60S particles that is essential for 60S ribosome biogenesis. Cryo-EM structures depict Nsa2 docked via its C-terminal β-barrel domain to nuclear pre-60S particles, whereas the extended N-terminus, consisting of three α-helical segments, meanders between various 25S rRNA helices with the extreme N-terminus in close vicinity to the Nog1 GTPase center. Here, we tested whether this unappreciated proximity between Nsa2 and Nog1 is of functional importance. Our findings demonstrate that a conservative mutation, Nsa2 Q3N, abolished cell growth and impaired 60S biogenesis. Subsequent genetic and biochemical analyses verified that the Nsa2 N-terminus is required to target Nsa2 to early pre-60S particles. However, overexpression of the Nsa2 N-terminus abolished cytoplasmic recycling of the Nog1 GTPase, and both Nog1 and the Nsa2-N (1-58) construct, but not the respective Nsa2-N (1-58) Q3N mutant, were found arrested on late cytoplasmic pre-60S particles. These findings point to specific roles of the different Nsa2 domains for 60S ribosome biogenesis.